The effect of ten-week FIFA 11+ injury prevention program for kids on performance and fitness of adolescent soccer players - Zarei, M.; Namazi, P.; Abbasi, H.; Noruzyan, M.; Mahmoodzade, S.; Seifbarghi, T (Asian Journal of Sports Medicine, 2018)
Background: Soccer is the world`s most popular sport, with most players being younger than 18 years. "FIFA 11+ Kids" has been recently introduced to prevent soccer injuries in adolescent players. This program would be more accepted and followed by coaches and players if it were to also promote performance and physical fitness in players. The purpose of this study was to assess the effect of a ten-week FIFA 11+ for kids Injury prevention program on performance and physical fitness in adolescent soccer players.